ANALISIS PENGARUH PERSEPSI HARGA, KEMUDAHAN PENGGUNAAN, DAN INTENSITAS PROMOSI TERHADAP PEMBUATAN KEPUTUSAN PEMBELIAN (Studi Empiris Pada Mahasiswa FEB Universitas Diponegoro Semarang Konsumen E-Commerce Shopee) - Ika Diah Nuraini; Retno Hidayati (Faculty of Economics and Business Diponegoro University, 2022)
The rapid development of technology today, resulting in many online businesses that have sprung up. These developments require companies to convince customers in making purchasing decisions for the goods sold. Related to this, the purpose of this study was to analyze the effect of price perception, ease of use, and promotion intensity on purchasing decision making for students of the Faculty of Economics and Business, Diponegoro University, Shopee e-commerce consumers in Semarang.The population used in this study were students of the Faculty of Economics and Business, Diponegoro University, Shopee e-commerce consumers in Semarang. In this study, the data collection method was carried out through a questionnaire from a sample of 120 respondents, using non-probability sampling and purposive sampling techniques. The data were processed and analyzed using multiple linear regression analysis with SPSS (Statistical Package for Social Science) version 25 program.The results showed that the perception of price has a positive and significant effect on making purchasing decisions. Ease of use has a positive and significant effect on making purchasing decisions. Promotion intensity has a positive and significant effect on making purchasing decisions.